Finales para Aluna [Endings for Aluna] by Selnich Vivas Hurtado: Decapitation,Masks andthedustoftheAmazonianBody - Uscátegui Narváez, Alexis (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The indigenous intellectual thought represented in Latin American novels operates as an anticolonial alternative to rethink the hegemonic States that attempt to subjugate national cultures. In this horizon, this article seeks to interpret the novel Finales para Aluna (2013) by Selnich Vivas, through different categories of analysis that enable us to understand its Amazonian content and highlight its importance in contemporary narrative